Dynamic Craniotomy With NuCrani Reversibly Expandable Cranial Bone Flap Fixation Plates: A Technical Report. Issue 1 (18th January 2023) - Khanna, Rohit; Munz, Michael; Baxter, Silvia; Han, Patrick
Abstract : BACKGROUND: Dynamic craniotomy provides cranial decompression without bone flap removal along with avoidance of cranioplasty and reduced risks for complications. OBJECTIVE: To report the first clinical cases using a novel dynamic craniotomy bone flap fixation system. The NeuroVention NuCrani reversibly expandable cranial bone flap fixation plates provide dynamic bone flap movement to accommodate changes in intracranial pressure (ICP) after a craniotomy. METHODS: The reversibly expandable cranial bone flap fixation plates were used for management of cerebral swelling in a patient with a subdural hemorrhage after severe traumatic brain injury and another patient with a hemorrhagic stroke. RESULTS: Both cases had high ICP's which normalized immediately after the dynamic craniotomy. Progressive postoperative cerebral swelling was noted which was compensated by progressive outward bone flap migration thereby maintaining a normal ICP, and with resolution of the cerebral swelling, the plates retracted the bone flaps to an anatomic flush position. CONCLUSION: The reversibly expandable plates provide an unhinged cranial bone flap outward migration with an increase in ICP and retract the bone flap after resolution of brain swelling while also preventing the bone flap from sinking inside the skull.